Soil mycobiota under managed and unmanaged forests of Nothofagus pumilio in Tierra del Fuego, Argentina - Elíades, Lorena (2019)
Background: Management practices can modify the productivity of forests and the associated microbial diversity of soil. The soil mycobiota is considered a key factor in the ecological functions of forests. Forests of Nothofagus pumilio (Poepp. & Endl.) Krasser (Nothofagaceae) are the main source of timber and one of the most important economic resources in the province of Tierra del Fuego (Argentina). However, there is no information on the impact of forest management interventions for the soil mycobiota, which can be reliable biological indicators of disturbance. Methods: Fungi were isolated from samples of soil collected under several Nothofagus pumilio forests subjected to different types of management and periods of time since the intervention. Types of management were represented by harvested forest with a shelter wood cutting, stockpile area and control forest without intervention and the periods of time since intervention were 1, 5–10 and 50 years. Species richness, evenness and Shannon’s diversity index of the mycobiota in each condition of management were calculated. Additionally, the effect of seasonality was analysed. Results: The soil mycobiota was represented by 70 taxa. Richness and/or Shannon’s diversity index of the mycobiota between undisturbed forest and stockpile area were higher in May (autumn) than in September or November. There were no differences in mycobiota diversity between dates in the harvested forest. Conclusions: Our results indicate that the forest intervention per se did not negatively affect the soil culturable mycobiota composition of N. pumilio forests in Tierra del Fuego (Argentina).